Hybrid Teaching: it proposes us to think about the digital connection, return plan and pedagogical practice (Research, Society and Development, 2022)
The study in focus in this article is part of an ongoing research with the objective of understanding the connection between the teacher training process and the interdisciplinary project, emphasizing the action-reflection-action of pedagogical practice. In this sense, we discuss the return plan for schools and the basic aspects that have been guiding the teacher's practice, as well as their professional training for execution. A qualitative approach is being used in this research, it is classified as exploratory based on its objective of providing greater familiarity with the problem. As for the procedures adopted, this research is a case study modality. As a research instrument we used the individual interview, focus group and document analysis. It is expected as a result, participation and dialogue about teamwork, which will be recognized as an important benefit for the articulation and effectiveness of the project as well as the studies and research that place the student at the center of the process, so that he takes the leading role in his learning. Thus, blended learning can be understood as a formal educational program.